Contribution to the knowledge of the bryophyte flora of the Lucanian side of the Pollino National Park. - Michele Aleffi; Annalena Cogoni; Carmine Colacino; Enza Evangelista; Sandro Perego; Maria Privitera; Marta Puglisi; Domenico Puntillo; Francesco Sguazzin; Roberta Tacchi; Silvia Poponessi (Italian Botanist, 2024)
The findings of the Bryological Excursion conducted by the Working Group for Bryology of the Italian Botanical Society from 5 to 8 July 2012 on the Lucanian side of the Pollino National Park are presented herein. The objective of the excursion was to address the paucity of knowledge regarding bryological diversity in understudied regions of Italy. This endeavour led to the discovery of 150 species of bryophytes, 41 of which are novel to the Basilicata region. For each species, the collection location and growth substrate are indicated. Some of the species are of floristic and phytogeographic interest. This is a group of boreal and arctic-alpine species, previously documented only in the Alpine arc and at the highest peaks of the Apennine chain. The Pollino massif represents the southernmost limit of their range. It is worth noting the presence of Brachydontium trichodes, Schistidium papillosum, Tortula laureri and Herzogiella striatella. Another noteworthy assemblage of species is found on the ophiolitic rocks of Timpa delle Murge. The distinctive ecological characteristics of this substrate result in the evolution of species that are exclusive to these environments. The ecological characteristics and distribution of each species within these two groups are described in detail.